2022
DOI: 10.3390/vaccines10071049
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of Asymptomatic Infections among SARS-CoV-2 Omicron Variant-Positive Individuals: A Systematic Review and Meta-Analysis

Abstract: Background: Asymptomatic infections are potential sources of transmission for coronavirus disease 2019, especially during the epidemic of the SARS-CoV-2 Omicron variant. We aimed to assess the percentage of asymptomatic infections among SARS-CoV-2 Omicron variant-positive individuals detected by gene sequencing or specific polymerase chain reaction (PCR). Methods: We searched PubMed, EMBASE, and Web of Science from 26 November 2021 to 13 April 2022. This meta-analysis was conducted following the Preferred Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 48 publications
1
71
2
1
Order By: Relevance
“…According to published reports, asymptomatic infections accounted for approximately 32.4%–45% of Omicron infections. 29 , 30 We observed highly diversified baseline neutralizing antibody titers to both Delta and Omicron variants prior to boosting with SCTV01C. About 90% of the participants showed positive PRNT50 (above lower limit of quantitation LLOQ: 20) of neutralizing antibody to live Omicron, which were much higher than previously reported for people vaccinated with two doses of mRNA vaccines.…”
Section: Discussionmentioning
confidence: 66%
“…According to published reports, asymptomatic infections accounted for approximately 32.4%–45% of Omicron infections. 29 , 30 We observed highly diversified baseline neutralizing antibody titers to both Delta and Omicron variants prior to boosting with SCTV01C. About 90% of the participants showed positive PRNT50 (above lower limit of quantitation LLOQ: 20) of neutralizing antibody to live Omicron, which were much higher than previously reported for people vaccinated with two doses of mRNA vaccines.…”
Section: Discussionmentioning
confidence: 66%
“…Several studies reported lower humoral immune responses after an infection with Omicron compared to other variants. This could be associated with milder symptoms caused by Omicron infections [27][28][29][30][31], since higher antibody levels and its persistence are correlated with disease severity in COVID-19 [15,16]. Recently, a study observed a lower humoral immune response after infection in Omicron convalescent individuals compared to individuals with two-dose mRNA vaccinations [14].…”
Section: Discussionmentioning
confidence: 99%
“…Between October 2021 and April 2022, these waves have cumulatively led to 310,308 cases of infection, corresponding to an estimated 35-40% of the general population [25,26]. Furthermore, infection with the Omicron variant is more commonly asymptomatic or paucisymptomatic [27][28][29][30][31] and therefore it is plausible that cases of Omicron infection more commonly remain undetected than infections with earlier variants, which suggests that the "true" number of cases is probably even higher. The impact of the high number of infections during winter 2021/2022 on the current seroepidemiological status of the population is likely to be substantial but remains to be determined reliably in an up-to-date seroepidemiological study.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, the pooled percentage of asymptomatic infections was 32.40% in Omicron. 30 We also checked the ability to test asymptomatic individuals. Most samples were collected under the Institutional Review Board of Seoul St. Mary's hospital (KC21TIDI0134K).…”
Section: Main Findingsmentioning
confidence: 99%